A Cell-Based High-Throughput Screening for Inducers of Myeloid Differentiation. (October 2015) - Radomska, Hanna S.; Jernigan, Finith; Nakayama, Sohei; Jorge, Susan E.; Sun, Lijun; Tenen, Daniel G.; Kobayashi, Susumu S.
Recent progress of genetic studies has dramatically unveiled pathogenesis of acute myeloid leukemia (AML). However, overall survival of AML still remains unsatisfactory, and development of novel therapeutics is required. CCAAT/enhancer binding protein α (C/EBPα) is one of the crucial transcription factors that induce granulocytic differentiation, and its activity is perturbed in human myeloid leukemias. As its reexpression can induce differentiation and subsequent apoptosis of leukemic cells in vitro, we hypothesized that chemical compounds that restore C/EBPα expression and/or activity would lead to myeloid differentiation of leukemic cells. Using a cell-based high-throughput screening, we identified 2-[( E )-2-(3, 4-dihydroxyphenyl)vinyl]-3-(2-methoxyphenyl)-4(3H)-quinazolinone as a potent inducer of C/EBPα and myeloid differentiation. Leukemia cell lines and primary blast cells isolated from human patients with AML treated with ICCB280 demonstrated evidence of morphological and functional differentiation, as well as massive apoptosis. We performed conformational analyses of the high-throughput screening hit compounds to postulate the spatial requirements for high potency. Our results warrant a development of novel differentiation therapies and significantly affect care of patients with AML with unfavorable prognosis in the near future.